Thermohydrodynamic analysis of foil journal bearings using differential quadrature method. (May 2016) - Bagheri, Maryam; Akbarzadeh, Saleh; Tikani, Reza; Raisivand, Masoud
The journal foil bearings are used in applications where a light load and a high speed are applied. Based on the internal structure of the foil bearing, various generations of these bearings have been developed. In order to determine the load capacity of the bearing, Reynolds equation and the energy equation are simultaneously solved to have a thermohydrodynamic analysis. Generalized differential quadrature method is used to solve the partial differential equations. Effect of parameters such as load and speed on the temperature of the bearing, the maximum pressure, and the load capacity is investigated. Best weighting coefficients and points' distribution are determined. Generalized differential quadrature method reduces the number of points of solution up to 80% and it also reduces the execution time. Published experimental and analytical data are used to validate the predicted results.